OUTCOMES OF DOSE ESCALATION WITH ADALIMUMAB (ADA) IN INFLAMMATORY BOWEL DISEASE. (8th June 2013) - Dillon, A; Rowan, C; Gibson, D; Keegan, D; Byrne, K; Mulcahy, H; Cullen, G; Doherty, G
Abstract : Introduction: Anti-TNF therapy is highly effective for induction and maintenance of remission in IBD. Subcutaneous agents such as adalimumab are licensed with a fixed dosing schedule irrespective of body weight. Aims/Background: We aimed to study the frequency and outcomes of dose escalation with adalimumab and evaluate any relationship to patient body weight. Method: A retrospective study of patients who commenced ADA therapy identified from a prospectively maintain database of >3.000 patients with IBD attending a single centre. Results: n=143 patients were identified who received adalimumab (ADA) for treatment of inflammatory bowel disease. 25 patients were excluded from the final analysis due to insufficient data. Data on n=118 patients were analysed (99 patients with Crohn's Disease, 18 patients with UC, one patient with IBD-U). 62/118 (53%) were male. 43/118 (36%) required dose escalation of ADA from every other week to weekly therapy. The median interval from initiation to dose escalation was 366 days (IQR 153 to 731). The mean body weight at initiation of therapy was similar between both groups (69.5 versus 69.9 kgs, p=ns). The time to dose escalation was not significantly associated with the use of concomitant immunomodulator therapy or with smoking history (current versus ex/never). 28/43 (65%) of patients who received dose escalation responded and 90% remain well on therapy with a median follow up of 1430 days (3.9 years). 15/43 (35%) failed to respond to dose escalation of whom 9 patients underwent surgery and 3 switched to another anti-TNF agent. The mean CRP at dose escalation was higher in the non-responders to to dose escalation than in the responder group (mean CRP 25.2 versus 9.1 mg/dL, p=0.05). Conclusion: Dose escalation with ADA is required in over a third of IBD patients but results in a sustained clinical response in the majority of cases. The study results suggests that an ADA dosing strategy based on measurement of ADA levels or inflammatory biomarkers rather than a weight based dosing strategy might help optimise results of therapy.